Pengaruh Latihan Proprioseptif terhadap Keseimbangan Pada Mahasiswa Setelah Cedera Ankle Ringan - Davidwin Simanungkalit; Nenny Saragi; Immanuel Panggabean; Nurhayati Simatupang (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Ankle injury is one of the most common musculoskeletal injuries among physically active university students, and one of its most detrimental functional consequences is a reduction in balance capacity due to impairment of the proprioceptive system. This study aimed to analyze the effect of proprioceptive training on improving balance among students of the Faculty of Sports Science, State University of Medan (FIKK Unimed) who had experienced mild ankle injuries. A quasi-experimental one-group pretest–posttest design was employed, involving 20 students who participated in an intervention program conducted twice per week for 8 weeks. Balance was assessed using a standardized functional balance test battery with scores ranging from 0 to 100. The results showed an increase in the mean balance score from 60.45 (pretest) to 68.70 (posttest), representing an average improvement of 8.25 points. A paired-samples t-test revealed a significant difference between pretest and posttest scores (t = 10.217, p = 0.000), with a Cohen’s d effect size of 2.28, indicating a large effect. These findings consistently demonstrate that structured proprioceptive training can significantly restore balance deficits following mild ankle injury and provide clinically meaningful improvements.